The microbial community and functional indicators response to flow restoration in gradient in a simulated water flume - Huang, Wei; Wang, Zhuowei; Liu, Xiaobo; Zhu, Dayu; Wang, Yurong; Wu, Leixiang (Frontiers in Microbiology, 2022)
Flow reduction has greatly affected the river ecological systems, and it has attracted much attention. However, less attention has been paid to response to flow restoration, especially flow restoration in gradient. Flow regime of rivers may affect river functional indicators and microbial community structure. This study simulated the ecological restoration of the flow-reduced river reach by gradiently controlling the water flow and explores the ecological response of environmental functional indicators and microbial community structure to the water flow. The results showed that gross primary productivity (GPP), ecosystem respiration rate (ER) and some water quality indices such as chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP), exhibited positive ecological responses to flow restoration in gradient. GPP and ER increased by 600.1% and 500.2%, respectively. The alpha diversity indices of the microbial community increased significantly with a flow gradient restoration. Thereinto, Shannon, Simpson, Chao1, and Ace indices respectively increased by 16.4%, 5.6%, 8.6%, and 6.2%. Canonical correspondence analysis (CCA) indicated that water flow, Dissolved oxygen (DO) and TP were the main influencing factors for changes in bacterial community structure. Microbial community structure and composition present a positive ecological response to flow restoration in gradient. This study reveals that the main variable in the restoration of the flow-reduced river reach is the flow discharge, and it provides a feasible scheme for its ecological restoration.